Transformasi Kepemimpinan dan Akuntabilitas Keselamatan dan Kesehatan Kerja (K3): Panduan Strategis Perubahan Budaya K3 di Lingkungan PT Pelabuhan Indonesia (Persero) - Bondan Winarno (Yayasan Literasi Sains Indonesia, 2026)
The port sector faces high Occupational Health and Safety (OHS) risks due to the complexity of operations involving human interaction, heavy equipment, and massive logistics. This study aims to analyze the operational risk profile of fatalities, formulate guidelines for K3 leadership roles across job levels, integrate Visible Felt Leadership (VFL) and GROW coaching model, and develop an accountability system based on leading and lagging indicators to realize a generative safety culture towards Zero Fatality at PT Pelabuhan Indonesia (Persero). This research employs a descriptive qualitative approach with strategic analysis based on safety culture transformation. The Safety Maturity Ladder model, Corporate Life Saving Rules (CLSR), and leadership role division serve as the main framework for developing operational strategic guidelines. The results show that 80–85% of accidents in container terminals are caused by human error. The implementation of Visible Felt Leadership (VFL) and GROW coaching proved effective in changing the mindset of leaders and workers. Structured leadership role guidelines along with the integration of leading indicators into management KPIs are the key to creating a robust safety culture. This study concludes that present, firm, and empathetic leadership is the main foundation for realizing a generative safety culture in the port environment. Keywords: Accountability of Safety, Leadership K3, Safety culture, Safety Maturity Ladder, Visible Felt Leadership